(untitled) (Journal of the College of Education for Women, 2024)
Iraqi learners need to enhance their proficiency in writing. Writing demands continuous development (Zsuzsi, 2017). Mastering the use of adjectives in English is important because it clarifies the target topic. Adjectives play an important role in making sentences clearer. Drawing upon Langacker’s Domain theory (1987), the researcher undertakes an experimental study involving 92 students from the University of Baghdad, College of Education for Women. The aim of this study is to improve writing skills via improving adjective usage. Quantitative data were gathered through two distinct tests – one administered at the commencement of the experiment and the other at its conclusion. Qualitative data were obtained through questionnaires, observations, and focus group discussions. Quantitative data were meticulously analyzed using the SPSS statistical editor and Excel sheet. The findings indicated that getting proficiency in using adjectives contributes to enhanced writing clarity among participants, fosters accuracy in depicting events, individuals, and locations, and empowers them to elaborate on details by leveraging the interconnected meanings.